2017
DOI: 10.1039/c7cc06860c
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(iii)-catalyzed intramolecular annulation through C–H activation: concise synthesis of rosettacin and oxypalmatime

Abstract: A flexible and efficient rhodium(iii)-catalyzed intramolecular annulation of benzamides bearing tethered alkynes for the synthesis of indolizinones and quinolizinones is reported. This reaction shows a broad substrate scope and excellent functional-group tolerance, including different kinds of heterocyclic substrates, such as furan, thiophene, pyrrole, benzofuran, benzothiophene, indole and isonicotinamide substrates. This method also provides a practical and efficient approach for the synthesis of rosettacin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…Tian and Van der Eycken published an intramolecular variant of this type of transformation ( Scheme 31E ). 222 This allowed them the synthesis of polycyclic systems which occurred in natural products as well. In their paper, they applied this method for building up a variety of polycycles in good to excellent yields, and also demonstrated the synthesis of two natural products, rosettacin and oxypalmatine.…”
Section: Monodentate Amides As Dgs In C–h Functionalisation Reactionsmentioning
confidence: 99%
“…Tian and Van der Eycken published an intramolecular variant of this type of transformation ( Scheme 31E ). 222 This allowed them the synthesis of polycyclic systems which occurred in natural products as well. In their paper, they applied this method for building up a variety of polycycles in good to excellent yields, and also demonstrated the synthesis of two natural products, rosettacin and oxypalmatine.…”
Section: Monodentate Amides As Dgs In C–h Functionalisation Reactionsmentioning
confidence: 99%
“…The reaction delivered a variety of tricyclic structures 63a – o that could be the core of some natural products (rosettacin, lycorine, etc.). The group of Eycken extended this methodology to the synthesis of tetracyclic skeletons, by using an alkyne tethered through an aromatic group . Results obtained by both groups highlight the versatility of the reaction, which showed excellent tolerance to functional groups and structural diversification.…”
Section: Intramolecular Coupling With Alkynesmentioning
confidence: 99%
“…We endeavored two catalytic systems based on ruthenium and rhodium, which in our laboratory have proven success in this type of cyclization [32,48]. First, the alkynylation protocol was attempted using the relatively cheap complex ( p -cymene)ruthenium(II) chloride dimer, in the presence of copper(II) acetate as oxidant under conventional heating.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Ackermann et al reported a Ru(II)-catalyzed synthesis of isoquinolones using an N -methoxyamide as directing group for the ortho -position and alkynyl bromide to achieve the regioselective cyclization (Scheme 1) [31]. In parallel, our group has developed Ru(II) and Rh(III)-catalyzed inter- and intramolecular annulations of aromatic rings with alkynes using a secondary amide as directing group (Scheme 1) [32,48]. In these protocols, the amide group plays a dual behavior of directing group and reaction center, as it participates in the final ring-closing reductive elimination.…”
Section: Introductionmentioning
confidence: 99%